Serum total protein and albumin levels among malnourished elementary-aged children East Nusa Tenggara, Indonesia - Marni Tangkelangi; Supriati Wila Djami; Michael Bhadi Bia; Aldiana Astuti (Public Health of Indonesia)
Background: School-aged children between 6-12 years are a vulnerable group that could be affected by malnutrition, which may cause growth failure and affect their school achievement. East Nusa Tenggara, Indonesia, is known as the province with the highest cases of malnutrition.